EFEKTIVITAS TANAMAN JAGUNG (Zea mays) DAN KACANG HIJAU (Vigna radiata) SEBAGAI MEDIA PEMBIAKAN FUNGI MIKORIZA ARBUSKULA (FMA) - Mony, Audy Yanti; Matinahoru, Johan; Hadijah, Miranda (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
Arbuscular mycorrhizal fungi (AMF) play a role in supporting the growth of various plants under certain conditions. AMF cannot survive in artificial media because they require a host plant for obligate symbiosis, which is necessary during the inoculum production process. The purpose of this study was to determine the effectiveness of corn and green bean roots as a breeding medium for arbuscular mycorrhizal fungi. The method used in this research used a two-factor completely randomized design (CRD). Observation of samples of the growth of corn and green bean seeds was carried out by observing samples placed on glass slides under a microscope. The results of the research showed that corn plants were more effective as a breeding medium for arbuscular mycorrhizal fungi (AMF) compared to green bean plants and the roots of corn plants were infected at a higher rate, namely 57.33% compared to the roots of green bean plants, namely 44.00%.